﻿Guide pratique des plantations d'arbres des forêts denses humides d'Afrique - Daïnou, Kasso (Uliège Library, 2021)
In Africa, tree plantations are likely to be developed for several reasons: restoration of production capacities and services provided by natural forests, enhancement of agroforestry lands, easier harvesting of wood and non-wood forest products, etc. As exotic species only provide specific services, it is important to revitalize the planting of local species. This is the purpose of this guide, which focuses on species of dense rainforests, capitalizing on the results of past and recent trials in six African countries, and on the This is the purpose of this guide, which focuses on species of dense rainforests, capitalizing on the results of past and recent trials in six African countries, and mobilizing individual skills and knowledge. The book provides a practical approach to the various stages of a silvicultural program: seed collection and management, nursery construction and management, and plantation installation and management. An estimate of the costs and profitability of such plantations is also provided. Finally, the book describes in detail the silvicultural itinerary of 50 tree species of the African rainforests. This guide is intended for a wide audience: managers, forestry technicians and engineers, students and scientists interested in tropical silviculture.